Transcriptomic analysis reveals the differentially expressed genes and pathways involved in drought tolerance in pearl millet [Pennisetum glaucum (L.) R. Br] - Dudhate, Ambika (PLoS One, 2018)
Pearl millet is a cereal crop known for its high tolerance to drought, heat and salinity stresses as well as for its nutritional quality. The molecular mechanism of drought tolerance in pearl millet is unknown. Here we attempted to unravel the molecular basis of drought tolerance in two pearl millet inbred lines, ICMB 843 and ICMB 863 using RNA sequencing. Under greenhouse condition, ICMB 843 was found to be more tolerant to drought than ICMB 863. We sequenced the root transcriptome from both lines under control and drought conditions using an Illumina Hi-Seq platform, generating 139.1 million reads. Mapping of sequenced reads against the foxtail millet genome, which has been relatively well-annotated, led to the identification of several differentially expressed genes under drought stress. Total of 6799 and 1253 differentially expressed genes were found in ICMB 843 and ICMB 863, respectively. Pathway and gene function analysis by KEGG online tool revealed that the drought response in pearl millet is mainly regulated by pathways related to photosynthesis, plant hormone signal transduction and mitogen-activated protein kinase signaling. The changes in expression of drought-responsive genes determined by RNA sequencing were confirmed by reverse-transcription PCR for 7 genes. These results are a first step to understanding the molecular mechanisms of drought tolerance in pearl millet and lay a foundation for its genetic improvement.